Digestion, faeces microbiome, and selected blood parameters in dogs fed extruded food containing Black soldier fly (Hermetia illucens) meal - Kanber Kara; Oğuzhan Kahraman; Fatma İnal; Zekeriya Safa İnanç; Sena Yilmaz Öztaş; M. Selçuk Alataş; Ibrar Ahmed (Italian Journal of Animal Science)
The aim of this study was to determine the effects of using black soldier fly (Hermetia illucens) (HI) at 0% (HI0), 7.5% (HI75) and 15% (HI150) larva meal instead of chicken meal in extruded dog food. A total of 18 Golden Retriever were used. In the study, HI larva meal was obtained and after detailed nutrient analysis, it was extruded as a dog food formulation instead of chicken meal. The foods were first subjected to in vitro digestion. Then, in vivo feeding in dogs was performed to determine preference test, digestion, blood variables and faecal microbiome, faecal score and organic acids. The HI larva meal up to 15% in dog food linearly increased the molarities of acetic (AA) and propionic (PA) acids in faeces (p <.05), but linearly decreased the molarities of butyric (BA) and valeric (VA) acids (p < 0.05). Iso-butyric (IBA), iso-valeric (IVA) and iso-caproic (ICA) acids in faeces decreased linearly with HI larva meal (p < .05). The relative abundances of Phascolarctobacterium, Megamonas, Collinsella and Fournierella genera were higher in faeces of HI75 than those of HI0 (p <.05). The relative proportion of Ligilactobacillus increased with HI larva meal (p < .05). As a result, HI larva meal can be used up to 100% instead of chicken meal in extruded dog food without any negative effects on body weight, digestibility, faecal score, consumption preference, kidney-liver enzyme activities and immunological parameters. Besides, HI larva meal at 7.5% and 15% in extruded dog food had different effects on the faecal microbiome.